Carbon Ion Radiotherapy Acts as the Optimal Treatment Strategy for Unresectable Liver Cancer During the Coronavirus Disease 2019 Crisis - Li, Zheng; Li, Qiang; Wang, Xiaohu; Li, Sha; Chen, Weiqiang; Jin, Xiaodong; Liu, Xinguo; Dai, Zhongying; Liu, Xiongxiong; Zheng, Xiaogang; Li, Ping; Zhang, Hui; et al. (Frontiers in Public Health, 2021)
The COVID-19 pandemic has greatly disrupted the normal treatment of patients with liver cancer and increased their risk of death. The weight of therapeutic safety was significantly amplified for decision-making to minimize the risk of SARS-CoV-2 infection. Herein, the safety and effectiveness of carbon ion radiotherapy (CIRT) for unresectable liver cancer (ULC) were evaluated, and Chinese experiences were shared to solve the predicament of ULC treatment caused by SARS-CoV-2. Worldwide studies were collected to evaluate CIRT for ULC as the world has become a community due to the COVID-19 pandemic. We not only searched five international databases including the Cochrane Library, Web of Science, PubMed, Embase and Scopus, but also performed supplementary retrieval with other sources. Chinese experiences of fighting against COVID-19 were introduced based on the advancements of CIRT in China and a prospective clinical trial of CIRT for treating ULC. A total of nineteen studies involving 813 patients with ULC were included in the systematic review. The qualitative synthetic evaluation showed that compared with transarterial chemoembolization (TACE), CIRT could achieve superior overall survival, local control and relative hepatic protection. The systematic results indicated that non-invasive CIRT could significantly minimize harms to patients with ULC and concurrently obtain superior anti-cancer effectiveness. According to the Chinese experiences, CIRT allows telemedicine within hospital (TMIH) to keep a sufficient person-to-person physical distance in the whole process of treatment for ULC, which is significant for cutting off the transmission route of SARS-CoV-2. Additionally, CIRT could maximize the utilization rate of hospitalization and outpatient care (UHO). Collectively, CIRT for ULC patients not only allows TMIH and the maximized UHO, but also has the compatible advantages of safety and effectiveness. Therefore, CIRT should be identified as the optimal strategy for treating appropriate ULC when we need to minimize the risk of SARS-CoV-2 infection and to improve the capacity of medical service in the context of the unprecedented COVID-19 crisis.